Introduction to the work of Cynthia Enloe - UNSW eLearning (2018)
VideoScribe animation that introduces the work of Cynthia Enloe and in particular her book "Bananas, Beaches and Bases: Making Feminist Sense of International Politics" in relationship to power, politics and International Relations. Scripted and read by Professor Laura Shepherd.
Keywords: approches et analyses; cours; discipline; histoire et politique; pol5480; premier cycle; rapports de pouvoir; ressource en ligne; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques